Proton affinities of didehydroporphyrin and subporphyrin in ground and excited states obtained by quantum chemical calculations - Glasovac, Zoran (Array, 2009)
Summary: Quantum-chemical calculations were used to investigate molecular and electronic properties of porphyrin and subporphyrin. Their basicities were estimated in ground and excited states. It was found that multiple proton - nitrogen lone-pair coordination plays an important role in acid/base properties of the studied molecules. Lone pair-lone pair interactions in didehydroporphyrin and energetic stabilization of its protonated form lead to the increase of a proton affinity compared to porphyrin by 18 kcal mol−1. A planarization of the protonated (dehydroporphyrin) structure leads to the complete reversal of the π-electron ring currents indicating aromaticity of the protonated form. On the other hand, calculations indicate that subporphyrin is slightly (by 5 kcal mol−1) more basic than porphyrin, which was explained by non-planar geometry, imposed by smaller ring size